Share this too : more social media solutions for PR professionals - Brown, Rob, 1962 December 17-; Waddington, Stephen; Chartered Institute of Public Relations (Chichester, West Sussex : Wiley, 2013)
This is a practical handbook to the changes taking place in the media and was conceived and written by 33 public relations practitioners using many of the social tools and techniques that it addresses. The book covered the media and public relations industry, planning, social networks, online media relations, monitoring and measurement, skills, industry change and the future of the industry.
The future of public relations. Digital PR is dead: social goes mainstream / Rob Brown -- The shift to conversation: content, context, and avoiding cheap talk / Dom Burch -- Content Frameworks: using content to achieve marketing communications goals / Robin Wilson -- Audiences and online habits. Planning : audiences, media and networks / Ged Carroll -- Digital anthropology / Kate Matlock -- Understanding social capital / Adam Parker -- The unsocial web / Dr. Mark Pack -- Conversations. Gamification: engaging audiences through play / Sharon O'Dea -- Community management / Paul Fabretti -- Curation / Michael Litman -- Live social events / Russell Goldsmith -- New channels, new connections / Mobile media / Stephen Davies -- To app or not to app? / Scott Seaborn -- The visual web / Dan Tyte -- Finding your way around: from Foursquare to Google Glass / Matt Appleby -- Connected employees / Kevin Ruck -- Professional practice. Social media and the law / Hanna Basha -- Online crisis management / Chris Norton -- Wikipedia and reputation management / Stephen Waddington -- The rise and rise of digital pharma / Becky McMichael -- Social in corporate communications / Rachel Miller -- Putting the social into corporate social responsibility / Stuart Bruce -- Building a personal brand online / Richard Bailey -- The social CEO / Jane Wilson -- Working across borders and boundaries / Julio Romo -- Business change and opportunities for the public relations industry. Laying the foundations for a social business / Jed Hallam -- Social commerce: show me the money / Katy Howell -- How to change organizational mindset / Gemma Griffiths -- The six influence flows / Philip Sheldrake -- Future proofing the public relations industry. Metrics that matter / Richard Bagnall -- Quantified self / Drew Benvie -- Network topology / Andrew Bruce Smith -- The public relations power of'big data' / Simon Collister.
Includes index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Public relations; Social media; Public relations; Social media; BUSINESS & ECONOMICS -- Advertising & Promotion; Public relations; Social media; Public relations; Social media; Electronic books